Monaco : Technical Note on IOSCO Objectives and Principles of Securities Regulation; Update. (IMF Staff Country Reports; Country Report ;, 2008)
This Technical Note reviews the International Organization of Securities Commissions's (IOSCO) Objectives and Principles of Securities Regulation for Monaco. It reveals that overall, there has been progress in implementing the Offshore Financial Center assessment recommendations in most areas of securities regulation, but more needs to be done on key topics. In granting a license to conduct investment activities, the Commission de Controle des Activites Financieres (Financial Activity Supervisory Commission) considers the professional qualifications of individuals, the company's systems and controls, and its sources of capital.